2011
DOI: 10.1007/s00401-011-0896-x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal accumulation of autophagic vesicles correlates with axonal and synaptic pathology in young Alzheimer’s mice hippocampus

Abstract: Dystrophic neurites associated with amyloid plaques precede neuronal death and manifest early in Alzheimer’s disease (AD). In this work we have characterized the plaque-associated neuritic pathology in the hippocampus of young (4- to 6-month-old) PS1M146L/APP751SL mice model, as the initial degenerative process underlying functional disturbance prior to neuronal loss. Neuritic plaques accounted for almost all fibrillar deposits and an axonal origin of the dystrophies was demonstrated. The early induction of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
209
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 189 publications
(251 citation statements)
references
References 68 publications
37
209
0
Order By: Relevance
“…Our data support the possibility that reactive astrocytes eliminate damaged synapses. The presence of several presynaptic markers at the plaque‐associated dystrophies (this work, Sanchez‐Varo et al, 2012, Trujillo‐Estrada et al, 2014) strongly suggests the presynaptic nature of these pathological structures. Similar findings have been also reported in another APP/PS1 model (Sadleir et al, 2016).…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Our data support the possibility that reactive astrocytes eliminate damaged synapses. The presence of several presynaptic markers at the plaque‐associated dystrophies (this work, Sanchez‐Varo et al, 2012, Trujillo‐Estrada et al, 2014) strongly suggests the presynaptic nature of these pathological structures. Similar findings have been also reported in another APP/PS1 model (Sadleir et al, 2016).…”
Section: Discussionsupporting
confidence: 53%
“…Also, we have reported that dystrophic neurites are APP‐positive and of axonal/synaptic nature (Sanchez‐Varo et al, 2012). However, besides the close spatial relationship between reactive astrocytes and amyloid plaques, there are no studies focusing on astroglia and the dystrophic neurites surrounding neuritic plaques.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations